Quality characteristics of wheat flour dough and bread containing grape pomace flour - Šporin, Monika; Avbelj, Martina; Kovač, Boris; Možina, Sonja Smole (Food science and technology international, 2018)
Wheat bread was enriched with 6%, 10% and 15% dried and milled grape pomace flour from two grape cultivars: 'Merlot' and 'Zelen'. Rheological, textural, sensory and antioxidant properties of the enriched dough and bread were evaluated, and compared to control samples. Grape cultivar had significant impact on the rheological characteristics of the dough, and on the sensory and antioxidant properties of the final bread. Development time and dough stability were longer when 'Merlot' grape pomace flour was added compared to 'Zelen' grape pomace flour and the control. Grape pomace flour addition affected bread volume, firmness, crumb and crust colour, and odour and taste intensity. Moreover, grape pomace flour addition resulted in a stickier and less springy crumb texture, and some negative sensorial properties, such as increased intensity of aftertaste and sand feeling in the mouth. The phenolic content and antioxidant activity of bread were positively correlated with grape pomace flour addition ( r = 0.987, p = 0.01 and r = 0.941, p = 0.01 between phenolic content and ferric reducing antioxidant power and phenolic content and 2,2-diphenyl-1-picrylhydrazyl, respectively). The highest total phenolic contents were 5.92 mg gallic acid equivalents (GAE)/g dw for 'Merlot' and 3.65 mg gallic acid equivalents /g dw for 'Zelen', which were seen for the bread prepared with the highest grape pomace flour addition (15%). The highest antioxidant activity determined by the 2,2-diphenyl-1-picrylhydrazyl and ferric reducing antioxidant power assays were seen for the bread prepared with the highest 'Merlot' grape pomace flour addition (15%). Dough characteristic and sensory profile are strongly influenced by cultivar of grape pomace flour. Based on results of sensory profiling, the variety 'Zelen' is suggested for use.